2008
DOI: 10.1021/la803152c
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Synthetically Valuable Biocatalysts into Polyelectrolyte Multilayer Systems

Abstract: Layer-by-Layer (LbL) technology recently turned out to be a versatile tool for the encapsulation of bioactive entities. In this study, the factual potential of this technology to encapsulate synthetically valuable biocatalysts, that is enzymes and whole cells expressing a specific catalytic activity, was investigated. The biocatalysts were embedded into a polyelectrolyte multilayer system involving poly(allylamine) hydrochloride (PAH) and poly(styrene sulfonate) sodium salt (PSS). The enzymes were adsorbed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
(83 reference statements)
2
19
0
Order By: Relevance
“…Previous studies with LbL assembled films have shown that enzyme activity typically decreases as they are placed in deeper layers due to reduced access of substrate through the covering layers of polyelectrolytes [9,10]. When enzymes such as lipase B and glucose oxidase have been incorporated into synthetic microcapsules the same observation has been made, with lower activity of enzyme in the core attributed to reduced mass transfer of substrate [11,12]. We have recently utilised the bioluminescent enzyme firefly luciferase to examine the influence that different locations in biodegradable microcapsules has on activity.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies with LbL assembled films have shown that enzyme activity typically decreases as they are placed in deeper layers due to reduced access of substrate through the covering layers of polyelectrolytes [9,10]. When enzymes such as lipase B and glucose oxidase have been incorporated into synthetic microcapsules the same observation has been made, with lower activity of enzyme in the core attributed to reduced mass transfer of substrate [11,12]. We have recently utilised the bioluminescent enzyme firefly luciferase to examine the influence that different locations in biodegradable microcapsules has on activity.…”
Section: Introductionmentioning
confidence: 76%
“…This structural organisation explains why in intact microcapsules D-luciferin substrate and co-factors (ATP and divalent cations) are slow to react with core luciferase. Studies performed by Wiemann et al (2009) with encapsulated enzymes noted that the polyelectrolyte capsule structure impacts on the mass transfer of substrates and/or products, and calculated a decrease of enzyme activity of about 10% per polyelectrolyte layer added [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the kinetic resolution of 1,2-O-isopropylidenglycerolesters, enantioselectivity dropped from 95% to 34% upon encapsulation. In contrast, the use of the same encapsulation protocol resulted in 1.32-fold increase in the activity of CalB (127).…”
Section: Layer-by-layer (Lbl) Structuresmentioning
confidence: 93%
“…These interactions can result in decreased intrinsic enzyme activity (e.g. creation of steric hindrance around the active site) or true inactivation (126,127). Benzaldehyde lyase from Pseudomonas fluorescens and alcohol dehydrogenase from Lactobacillus brevis showed almost no activity after encapsulation into PAH/PSS microcapsules.…”
Section: Layer-by-layer (Lbl) Structuresmentioning
confidence: 99%
“…AnsorgeSchumacher and coworkers very recently pointed out the importance of the combination of capsules' polyelectrolyte, reactants, and enzyme [232]. The biocatalysts (lipase B) were adsorbed to CaCO 3 or DEAE-cellulose colloidal cores on which LbL multilayers of PAH and PSS had been coated.…”
Section: Lbl Assembly On Colloidal Particlesmentioning
confidence: 99%